ANALYSIS OF BPJS PATIENT SATISFACTION LEVEL TOWARDS COMMUNITY HEALTH CENTER HEALTH SERVICES - Ndruru, Efranita Somasi Crownlina; Asriwati, Asriwati; Subaedah, Sitti (Universitas Prima Indonesia, 2024)
High patient satisfaction will indicate how well the health center is able to provide high-quality medical care. The Service Quality Approach (SERVQUAL) can be used to measure the level of patient satisfaction consisting of fitness, assurance, physical evidence, empathy, and responsiveness. This study examines how satisfied BPJS patients are with medical services. This study was conducted at the Bawomataluo Health Center in Fanayama District. Sampling was carried out using the Accidental Sampling method totaling 99 people. The results of the study showed the influence of reliability, assurance), real evidence, empathy, and no influence of responsiveness to health services. The conclusion of this study is that there is no influence when viewed from the five dimensions in terms of performance level, but there is an influence when viewed from the aspects of completeness, assurance, physical evidence, empathy, and responsibility on the level of BPJS patient satisfaction with health services. It is hoped that the Health Center can improve patient happiness, including attention from health workers who are very important in meeting patient needs to get special care.